Pemanfaatan lahan pekarangan untuk mendukung kemandirian pangan di Desa Mundu, Klaten, Jawa Tengah - Perwithosuci, Winny; Andriyani, Nur; Hidayah, Nur; Oftasari, Yosi; Qomarun, Qomarun; Kisnawaty, Sudrajah Warajati (Nur Science Institute, 2024)
The planting schedules and harvest quality have changed due to climate change. Consequently, the harvest yields occasionally fail to meet the market's demands and threaten food security. This situation will lead to an increase in food prices and also impact other health issues, such as stunting. Therefore, the aim for food security remains an important project to enhance national development. The community service team from the Muhammadiyah University of Surakarta, in partnership with the Mundu Village Government in Klaten Regency, organized a series of service activities to enhance food security through the